"All we want are toilets inside our homes!" The critical role of sanitation in the lives of urban poor adolescent girls in Bengaluru, India. (April 2015) - Nallari, Anupama
This paper describes how lack of access to adequate sanitation facilities affects the lives of adolescent girls in urban poor India. It draws specifically on the experiences of four adolescent girls, each living in one of four settlements in Bengaluru, India, and conversations with a larger group of girls. Findings reveal that where sanitation facilities are sorely lacking, adolescent girls face many deprivations (education, free time, privacy and independent mobility) and risks (sexual harassment and assault, health risks, etc.), and that this inadequacy can be a structural pathway for cyclical gender-based disempowerment and injustice.